2020
DOI: 10.1332/204674319x15536817073756
|View full text |Cite
|
Sign up to set email alerts
|

Tracing pathways of relatedness: how identity-release gamete donors negotiate biological (non-)parenthood

Abstract: This article draws on an interview study with UK ‘identity-release’ sperm and egg donors, exploring how, in the context of a new ethic of openness around donor conception, they articulate their role in relation to offspring. I show that participants neither dismissed, nor straightforwardly activated, the relational significance of the ‘biological’ substance they donated. Instead, they renegotiated its meaning in ways which do not map straightforwardly on to established kinship roles. Building on a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“… Mohr’s (2015) ethnographic research with Danish sperm donors found that despite being encouraged by sperm bank staff to think of their donation in purely contractual terms, those who chose to be identity-release donors were clear that they had a role in relation to their donor-conceived offspring. Similarly to the gamete donors in Gilman’s (2019) study, however, they found it difficult to articulate what this role might be, envisaging a socially meaningful, but non-parental, relationship with their donor offspring. Naming connections and determining obligations to individuals to whom one is genetically connected yet socially disconnected, Mohr argues, causes sperm donors to engage reflectively in an intricate play of connecting and disconnecting the social and the biological, and in doing so coming up with their own ways of acknowledging the social significance of the biogenetic connections established through donor conception.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“… Mohr’s (2015) ethnographic research with Danish sperm donors found that despite being encouraged by sperm bank staff to think of their donation in purely contractual terms, those who chose to be identity-release donors were clear that they had a role in relation to their donor-conceived offspring. Similarly to the gamete donors in Gilman’s (2019) study, however, they found it difficult to articulate what this role might be, envisaging a socially meaningful, but non-parental, relationship with their donor offspring. Naming connections and determining obligations to individuals to whom one is genetically connected yet socially disconnected, Mohr argues, causes sperm donors to engage reflectively in an intricate play of connecting and disconnecting the social and the biological, and in doing so coming up with their own ways of acknowledging the social significance of the biogenetic connections established through donor conception.…”
Section: Introductionmentioning
confidence: 89%
“…Surprisingly little is known about UK sperm donors and their thoughts and feelings about the removal of anonymity and being an identity-release donor. Drawing on her qualitative research with egg and sperm donors in Scotland, Gilman (2019) showed how the identity-release gamete donors neither dismissed, nor straightforwardly activated, the relational significance of the ‘biological substance’ they donated. She showed how donors grappled with a lack of suitable vocabulary with which to describe their relationship to children conceived from their donation and struggled to articulate why this connection was significant, despite most stating that it was.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies into egg donation were rare, but tended to focus more on experiences (Konrad, 2005;Shaw, 2007). Since the mid-2000s, research into egg and sperm donors' experiences has expanded with important emerging foci being around potential exploitation, reproductive labour and racialised and economic inequalities (Nahman, 2013;Waldby, 2019); donation and enactments of gender (Almeling, 2011;Mohr, 2018); and also the relational consequences of donation, particularly between the donor and the recipient family (Andreassen, 2019;Gilman, 2020;Hertz & Nelson, 2019;Petersen, 2019). The latter is also the home of our study, which is the first qualitative study to situate donation in the context of donors' own relationships.…”
mentioning
confidence: 99%